Pengaruh Jumlah Pengajuan Penutupan dan Premi Asuransi Kebakaran terhadap Laba Bersih pada PT. Bosowa Asuransi Cabang Jakarta Kota - Laksono, Ferdi; Kurniawan, Y. Jhony; Addini, Fida Fathiyah (Premium Insurance Business Journal, 2024)
This research aims to analyze the influence of the number of closing applications and fire insurance premiums on the net profit of PT. Bosowa Insurance Jakarta City Branch. This research uses quantitative data analysis methods by collecting data from insurance transaction records from June 2022 to April 2024. The collected data is analyzed using multiple linear regression methods to identify the relationship between the independent variables (Number of Closing Applications and Fire Insurance Premiums) and the dependent variable (Profit Clean). The results of the research show that there is an influence of the Number of Closing Applications on Net Profit, while the effect of Fire Insurance Premiums on Net Profit is temporary and not strong. The implication of this research is the importance of management in managing the number of Closing Applications and Fire Insurance Premiums to increase Net Profit at PT. Bosowa Insurance Jakarta City Branch.